(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
The study conducted between 2000 and 2007 in two cereal environments near Boudouaou and Corso, in the eastern part of Mitidja on estimation of damage caused by the hybrid sparrow on the stubble fields of wheat and barley crops shows that the plots to attack by individuals of Passer domesticusx P. hispaniolensisare those that are in their environment perch trees, water points and houses. Through the partial correlationsand the simple correlations, the damage is significantly related to the abundance of perch, houses and water points. For this purpose, this study confirms that losses caused by this bird vary from one plot to another, while taking account of the colony, the presence or absence of water sources and high or low abundance of perches.